2019
DOI: 10.1093/pm/pnz008
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a Hybrid Web-Based and In-Person Self-management Intervention Aimed at Preventing Acute to Chronic Pain Transition After Major Lower Extremity Trauma (iPACT-E-Trauma): A Pilot Randomized Controlled Trial

Abstract: Objective 1) To assess the feasibility of research methods to test a self-management intervention aimed at preventing acute to chronic pain transition in patients with major lower extremity trauma (iPACT-E-Trauma) and 2) to evaluate its potential effects at three and six months postinjury. Design A pilot randomized controlled trial (RCT) with two parallel groups. Setting A supraregional level 1 trauma center. Methods Fifty-six adult patients were randomized. Partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 96 publications
0
17
0
Order By: Relevance
“…We included 18 trials in the qualitative synthesis. 27,28,44,[63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78] However, only 11 trials, were included in the meta-analysis based on the possibility of using data as analyzed and the unavailability of required data from some trials' authors. 27,67,68,[74][75][76][77] These trials were published 8 to 33 years before the conduction of the meta-analyses and authors no longer had access to their database, did not answer us when we contacted them, or could not be reached.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We included 18 trials in the qualitative synthesis. 27,28,44,[63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78] However, only 11 trials, were included in the meta-analysis based on the possibility of using data as analyzed and the unavailability of required data from some trials' authors. 27,67,68,[74][75][76][77] These trials were published 8 to 33 years before the conduction of the meta-analyses and authors no longer had access to their database, did not answer us when we contacted them, or could not be reached.…”
Section: Resultsmentioning
confidence: 99%
“…and a research assistant) using a "risk of bias table" in DistillerSR developed according to the criteria outlined in the Cochrane Handbook for Systematic Reviews of Interventions. 41,43 One of the selected trials was performed by the first author 44 and she was therefore not involved in the assessment of risk of bias for this trial. Judgment of high, low, or unclear bias was made.…”
Section: Assessment Of Risk Of Bias In Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This model also appeared to be useful when the COVID-19 pandemic forced (orthopedic) outpatient clinics to limit face-to-face consultations [ 11 ]. Another concept aimed to prevent persistent pain symptoms after lower extremity injuries with web-based cognitive behavioral interventions supported by a nurse [ 12 , 13 ]. A preliminary randomized feasibility trial showed less pain intensity in comparison with the provision of an educational pamphlet.…”
Section: Introductionmentioning
confidence: 99%
“…Traumatic injuries and their surgical management often result in high-intensity pain, 1 12 usually requiring opioids for pain relief. 13 , 14 Nevertheless, up to 20% of patients with traumatic injuries become long-term opioid users (≥ three months) 15 – 19 and this percentage may climb to 60% in those with risk factors such as mental health problems, a history of substance use problems, or living with chronic pain.…”
mentioning
confidence: 99%